2007
DOI: 10.1186/1475-2867-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 sensitizes rat pituitary adenoma GH3 cells to bromocriptine induced apoptosis

Abstract: BackgroundProlactinoma is the most frequent pituitary tumor in humans. The dopamine D2 receptor agonist bromocriptine has been widely used clinically to treat human breast tumor and prolactinoma through inhibition of hyperprolactinemia and induction of tumor cell apoptosis, respectively, but the molecular mechanism of bromocriptine induction of pituitary tumor apoptosis remains unclear. Caveolin-1 is a membrane-anchored protein enriched on caveolae, inverted flask-shaped invaginations on plasma membranes where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Lee et al [55] also provided evidence that tyrosine-kinase signaling is regulated by tyrosine-phosphorylated Cav-1. Jiang et al [56] suggested that the phosphorylation of Cav-1 at the tyrosine Y14 terminus after bromocriptine treatment may contribute to the sensitization of apoptosis in GH3 cells that have been exposed to bromocriptine. In the same year, Shajahan et al [57] showed that the Src phosphorylation of Tyr 14 on Cav-1 regulates paclitaxel-mediated apoptosis in MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [55] also provided evidence that tyrosine-kinase signaling is regulated by tyrosine-phosphorylated Cav-1. Jiang et al [56] suggested that the phosphorylation of Cav-1 at the tyrosine Y14 terminus after bromocriptine treatment may contribute to the sensitization of apoptosis in GH3 cells that have been exposed to bromocriptine. In the same year, Shajahan et al [57] showed that the Src phosphorylation of Tyr 14 on Cav-1 regulates paclitaxel-mediated apoptosis in MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Employing GH3 cells multiple reports show that DA and/or BC induce apoptosis [7,13,16,18,35]. Perhaps due to the importance of DA in pituitary physiology and homeostatic control mechanisms the characterisation of DA-mediated apoptosis has received particular recent attention in these cells [7] and also in primary rodent pituitaries and lactotrophs [14].…”
Section: Discussionmentioning
confidence: 99%
“…In common with multiple previous reports [7,13,16,17,18,31,32] a cell line model system was chosen on the basis that it circumvented likely complications associated with determining effects within the admix of cell types that comprise the normal pituitary gland. Despite the advantages afforded by this in vitro system we recognise that the concentrations of BC used in our experiments are significantly higher than C max values observed in patients following oral drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations could lead to changes in the amount of T-cells which play a key role in both cellular and hemoral immune systems (Elenkov et al, 2000). T-cells control the natural tumor cells via secretion of cytokines TNF-α (Jiang et al, 2007). Thus, the coordinated over expression of DRD2 family receptor genes enhances each other (additive effect) and leads to reduction of T-cells amount.…”
Section: Discussionmentioning
confidence: 99%